(untitled) (European Bison Conservation Newsletter, 2019)
The Bison Breeding Center in the Oka Reserve was established in 1959 and covers an area of 180 hectares. In this work, we used data on 526 individuals for the period from 1960 to 2018, grouped into 3 age groups: calves up to one year old, young E. bison from 1 to 3 years old, adult animals 3 years old and older (males and females). The dynamics of the sex and age structure for particular age groups was analyzed. Over the entire period, 441 E. bison were born in the nursery, their sex ratio was: 52.6% of males and 47.4% of females. In the group of adult animals, there is a sharp disproportion between sexes, with a predominance of females (25.4% and 74.6%), on average, per 1 male there are 3 females. Analysis of annuall data on the age and sex structure of the European bison group in the Oka Reserve from 1962 to 2018 showed the following ratio: adult males – 13.9%, adult females – 41.2%, young animals – 26.0% and calves – 18.9%. The formation of sex and age structure in the natural groups of E. bison and in the nursery is different. Comparison of data showed that the proportion of calves in the nursery is higher than in nature (respectively 19% and 14%) due to the greater number of adult breeding females. The share of young wisent is equal with free population of E. bison of the Belovezhskaya Pushcha of Byelarus (26% and 26%). The representation of adult females in the nursery is higher than in nature (41% and 39%), and the representation of adult males is lower (14% and 21%), due to the number of males in the nursery limited or not participating in breeding. For the optimal sex and age structure of E. bison group at the nursery, the following proportion can be considered: calves – 20%, young wisent – 25%, adults – 55% (males – 15%, females – 40%).